Increase in the prevalence of mutations associated with sulfadoxine–pyrimethamine resistance in Plasmodium falciparum isolates collected from early to late pregnancy in Nanoro, Burkina Faso - Esmée Ruizendaal; Marc C. Tahita; Ronald B. Geskus; Inge Versteeg; Susana Scott; Umberto d’Alessandro; Palpouguini Lompo; Karim Derra; Maminata Traore-Coulibaly; Menno D. de Jong; Henk D. F. H. Schallig; Halidou Tinto; et al. (Malaria Journal, 2017)
Abstract Background Pregnant women are a high-risk group for Plasmodium falciparum infections, which may result in maternal anaemia and low birth weight newborns, among other adverse birth outcomes. Intermittent preventive treatment with sulfadoxine–pyrimethamine during pregnancy (IPTp-SP) is widely implemented to prevent these negative effects of malaria. However, resistance against SP by P. falciparum may decrease efficacy of IPTp-SP. Combinations of point mutations in the dhps (codons A437, K540) and dhfr genes (codons N51, C59, S108) of P. falciparum are associated with SP resistance. In this study the prevalence of SP resistance mutations was determined among P. falciparum found in pregnant women and the general population (GP) from Nanoro, Burkina Faso and the association of IPTp-SP dosing and other variables with mutations was studied. Methods Blood spots on filter papers were collected from pregnant women at their first antenatal care visit (ANC booking) and at delivery, from an ongoing trial and from the GP in a cross-sectional survey. The dhps and dhfr genes were amplified by nested PCR and products were sequenced to identify mutations conferring resistance (ANC booking, n = 400; delivery, n = 223; GP, n = 400). Prevalence was estimated with generalized estimating equations and for multivariate analyses mixed effects logistic regression was used. Results The prevalence of the triple dhfr mutation was high, and significantly higher in the GP and at delivery than at ANC booking, but it did not affect birth weight. Furthermore, quintuple mutations (triple dhfr and double dhps mutations) were found for the first time in Burkina Faso. IPTp-SP did not significantly affect the occurrence of any of the mutations, but high transmission season was associated with increased mutation prevalence in delivery samples. It is unclear why the prevalence of mutations was higher in the GP than in pregnant women at ANC booking. Conclusion The high number of mutants and the presence of quintuple mutants in Burkina Faso ...